2011
DOI: 10.3389/fimmu.2011.00033
|View full text |Cite
|
Sign up to set email alerts
|

The Human Cutaneous Chemokine System

Abstract: Irrespective of the immune status, the vast majority of all lymphocytes reside in peripheral tissues whereas those present in blood only amount to a small fraction of the total. It has been estimated that T cells in healthy human skin outnumber those present in blood by at least a factor of two. How lymphocytes within these two compartments relate to each other is not well understood. However, mounting evidence suggest that the study of T cell subsets present in peripheral blood does not reflect the function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 196 publications
(152 reference statements)
0
23
0
2
Order By: Relevance
“…CCR8 expression in human blood leukocytes is scarce and largely restricted to central and effector memory ␣␤ T cells 25,28,29 ( Figure 1A-B), despite previous reports claiming a broader distribution (reviewed by McCully and Moser 24 ). In agreement with our earlier studies, 23,30 we found that CCR8 is preferentially expressed on T cells present in healthy human skin (49.5% Ϯ 5.8%; n ϭ 7; Figure 1A) compared with those present in blood (5.05% Ϯ 1.53%; n ϭ 14), and have a predominant effector memory (CD45RA Ϫ CCR7 Ϫ ) phenotype, although for some donors a significant fraction of CD8 ϩ T cells were terminally differentiated as characterized by CD45RA re-expression (Temra; Figure 1B).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…CCR8 expression in human blood leukocytes is scarce and largely restricted to central and effector memory ␣␤ T cells 25,28,29 ( Figure 1A-B), despite previous reports claiming a broader distribution (reviewed by McCully and Moser 24 ). In agreement with our earlier studies, 23,30 we found that CCR8 is preferentially expressed on T cells present in healthy human skin (49.5% Ϯ 5.8%; n ϭ 7; Figure 1A) compared with those present in blood (5.05% Ϯ 1.53%; n ϭ 14), and have a predominant effector memory (CD45RA Ϫ CCR7 Ϫ ) phenotype, although for some donors a significant fraction of CD8 ϩ T cells were terminally differentiated as characterized by CD45RA re-expression (Temra; Figure 1B).…”
Section: Resultsmentioning
confidence: 58%
“…19,20 Our findings support a model that places healthy skin tissue at the helm of skin-tropic T PS regulation. 24 It moves the attention away from local DCs, which on their own are relatively poor inducers of CCR8, and emphasizes the role of stable soluble factor(s) produced by keratinocytes that act directly on activated T cells. We propose that drainage of these factor(s) together with antigen, either in free (unprocessed) form or captured by migrating DCs, into adjacent lymph nodes results in CCR8 and CLA expression in responding T cells.…”
Section: Regulation Of Ccr8 Expression By Keratinocytes 4595mentioning
confidence: 99%
See 1 more Smart Citation
“…CD43 and CD44 expressed by T cells can also act to engage E-selectin. Although many chemokines can participate in migration of effector T cells to the skin depending on the characteristics of the infection or inflammation (50), the capacity for recruitment of effector T cells to the skin is primarily associated with expression of CCR8 and CCR10. While skin T cells express high levels of CCR4 and its ligands CCL17 and CCL22 are produced by epidermal keratinocytes and dermal fibroblasts, skin DC have not been shown to imprint CCR4 expression, which suggests that this MR is not exclusively a skin-homing molecule.…”
Section: Distinct Mr Expression Profiles Determine Tissue-specific MImentioning
confidence: 99%
“…Extensive evidence demonstrates the ability of local dendritic cell populations to influence the migration of T-cells to the gut and skin [22][23][24][25]. Whether this also holds true for T-cell migration to the respiratory tract is less clear.…”
Section: Effect Of Local Pro-inflammatory Signals On the Distributionmentioning
confidence: 99%